Teammate Familiarity in Distributed Computer-Supported Collaborative Learning: The Mediating Role of Social Presence - Zhang, Shunan; Nan, Dongyan; Sun, Seungjong; Che, ShaoPeng; Kim, Jang Hyun (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Owing to the limitations of computer-mediated communication (CMC), distributed CSCL (Computer-supported collaborative learning) has not always been as effective as desired. Despite recognizing the significance of group composition, the exploration of the function of teammate familiarity in distributed educational settings is restricted. This study explored the influence of teammate familiarity and social presence in a distributed CSCL setting by conducting an online survey of 288 Korean university students with experience in distributed CSCL. The results indicate that teammate familiarity increased the social presence experienced by students among their peers. Social presence subsequently enhanced teamwork satisfaction and, ultimately, increased self-assessed knowledge gain. More importantly, the relationship between teammate familiarity and teamwork satisfaction was mediated by social presence. Social media platforms and class webpages were the most widely used channels for students to get to know their teammates. Our study provided insights for improving the effectiveness of distributed CSCL and a framework for investigating social presence in satisfaction building in various contexts, including online education.